2016
DOI: 10.1177/1534735416668575
|View full text |Cite
|
Sign up to set email alerts
|

Interest in Integrative Medicine Among Postmenopausal Hormone Receptor–Positive Breast Cancer Patients in the EvAluate-TM Study

Abstract: Background. Breast cancer patients often use complementary and alternative medicine, but few prospectively collected data on the topic are available specifically for postmenopausal breast cancer patients. A large prospective study was therefore conducted within a noninterventional study in order to identify the characteristics of patients interested in integrative medicine. Methods. The EvAluate-TM study is a prospective, multicenter noninterventional study in which treatment with the aromatase inhibitor letro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 48 publications
3
37
1
2
Order By: Relevance
“…Patients' characteristics significantly associated with the wish for integration of complementary healing approaches are mainly the same, namely age, education, employment, and usage of CAM. This is concordant with the literature [5,6,8,39] and suggests that patients inclined towards one of the supportive services are very likely to be interested in integrative medicine in general.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Patients' characteristics significantly associated with the wish for integration of complementary healing approaches are mainly the same, namely age, education, employment, and usage of CAM. This is concordant with the literature [5,6,8,39] and suggests that patients inclined towards one of the supportive services are very likely to be interested in integrative medicine in general.…”
Section: Discussionsupporting
confidence: 81%
“…The scarce coverage of the demand for supportive care services is a phenomenon not seldom observed in the literature [5,6,35,36]. Despite conspicuous interest among patients as well as growing acceptance among physicians, a persistent lack of implementation of integrative medicine into standard cancer care in Germany has been reported [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study mainly including postmenopausal patients with early breast cancer found that 69% of the patients were physically active, 87% paid attention to nutrition, and 46% used CAM [34]. Almost 50% of postmenopausal BC patients treated with an AI are interested in CAM [33]. An Australian study investigating strategies for managing aromatase inhibitor musculoskeletal syndrome (AIMSS), including CAM, noted only limited effectiveness of CAM in patients who had AIMSS [13].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the breast cancer patients show high interest in CAM [13, 14]. However, little is known about the acceptance and use of integrative medicine by gynecological oncologists in Germany.…”
Section: Introductionmentioning
confidence: 99%